Do financial counseling mandates improve mortgage choice and performance? Evidence from a legislative experiment - Sumit Agarwal; Gene Amromin; Itzhak Ben-David; Souphala Chomsisengphet; Douglas D. Evanoff (Federal Reserve Bank of Chicago, 2009)
We explore the effects of mandatory third-party review of mortgage contracts on the terms, availability, and performance of mortgage credit. Our study is based on a legislative experiment in which the State of Illinois required 'high-risk' mortgage applicants acquiring or refinancing properties in 10 specific zip codes to submit loan offers from state-licensed lenders to review by HUD-certified financial counselors. We document that the legislation led to declines in both the supply of and demand for credit in the treated areas. Controlling for the salient characteristics of the remaining borrowers and lenders, we find that the ex post default rates among counseled low-FICO-score borrowers were about 4.5 percentage points lower than those among similar borrowers in the control group. We attribute this result to actions of lenders responding to the presence of external review and, to a lesser extent, to counseled borrowers renegotiating their loan terms. We also find that the legislation pushed some borrowers to choose less risky loan products in order to avoid counseling.
Keywords: D14; D18; L85; R21; 330; Financial literacy; Counseling; Subprime crisis; Household finance; Finanzmarktkrise; Subprime-Hypothek; Refinanzierung; Haushaltsökonomik; Kreditpolitik; USA